Kepatuhan Protokol APD Pada K3 dan Kinerja Karyawan Instalasi Radiologi RSUD dr. Saiful Anwar Malang - Agus Sulistianto (Poltekkes Kemenkes Semarang, 2022)
Background: Occupational Safety and Health (K3) is one of the labor protection systems to prevent and reduce the occurrence of health problems and accidents caused by dangerous environments and ways of working. Preventing these hazards and damages, safety is a very important factor so that it can reduce the risk due to work in radiology installations by using radiation protection. The purpose of the study is to know the impact of APD protocol compliance on employee safety, health and performance.Methods: Research design uses qualitative deskriotive methods. The selection of informants was obtained from observations and interviews to employees of radiology installations of dr. Saiful Anwar Malang Hospital. The study used purposive sampling techniques. Research instruments use observation sheets, interview guidelines and documentation study sheets. The study was conducted in November 2021 at dr. Saiful Anwar Malang Hospital.Results: The results showed radiology unit officers had compliance with APD usage protocols that impacted employee safety and occupational health. Radiology Installation Officer dr. Saiful Anwar Malang has implemented employee work safety and has compliance with occupational health. Radiology Installation Officer of rsud dr. Saiful Anwar Malang has an excellent performance.Conclusions: The results of this study can be used as a reference by health workers to measure the level of compliance in the use of PPE, as well as to improve the knowledge and attitude of health workers in using PPE. The institution is expected to further increase supervision on radiographers, especially in working to be more disciplined in implementing the use of PPE.